Controlled release of 1-methylcyclopropene from its functionalised electrospun fibres under constant and linearly ramped humidity. Issue 10 (3rd October 2017) - Neoh, Tze Loon; Ariyanto, Hermawan Dwi; Menéndez Galvan, Patricia; Yoshii, Hidefumi
ABSTRACT: The methodology to electrospin polystyrene (PS) fibres functionalised with the inclusion complex between 1-methylcyclopropene (1-MCP) and α-cyclodextrin (α-CD) has been developed successfully. Due to limited availability, α-CD crystals instead of 1-MCP/α-CD complex were suspended in the electrospinning (ES) solutions to investigate the ES process. The ES solutions were characterised in terms of viscosity, conductivity and surface tension. Meanwhile, the fibres were subjected to scanning electron microscopy. The average fibre diameter was proportional to approximately one-sixth power of the capillary number of the ES solution. Viscosity, which was a function of PS concentration and α-CD loading, was the main property that dictated the spin ability of the ES solutions. ES fibres with 1.5–4.4 μm in diameter were produced with 12.5–20.0% (w/w) PS in ES solution and an equal amount of the inclusion complex for PS. In the case of the ES solutions of 20 wt% PS loaded with the inclusion complex from 0 to 100% (w/w) to PS, all the ES solutions were electrospinnable with the average diameter ranging from 3.8 to 4.6 μm. X-ray diffractometry indicated that the α-CD crystals were homogeneously suspended on the fibre mats. Confocal laser scanning microscopy showed that the crystals were suspended on the fibre mats while being coated with a layer of PS. The complex-functionalised fibre was formed from the ES solution of 20% PS and 50% (w/w) inclusion complex with the ES. The release characteristics of 1-methylcyclopropene (1-MCP) from the functionalised fibre and the inclusion complex were investigated real time under linearly ramping humidity conditions at constant temperatures with a home-built humidity regulating system coupled with gas chromatography. The irregular release profiles were successfully modelled and the activation energies of release for the functionalised fibre and inclusion complex were about 128 and 69 kJ/mol, respectively.. Graphical Abstract: